Chemically programmed STING-activating nano-liposomal vesicles improve anticancer immunity - Chen, Xiaona; Meng, Fanchao; Xu, Yiting; Li, Tongyu; Chen, Xiaolong; Wang, Hangxiang (Nature communications, 2023)
The often immune-suppressive tumor microenvironment (TME) may hinder immune evasion and response to checkpoint blockade therapies. Pharmacological activation of the STING pathway does create an immunologically hot TME, however, systemic delivery might lead to undesired off-target inflammatory responses. Here, we generate a small panel of esterase-activatable pro-drugs based on the structure of the non-nucleotide STING agonist MSA-2 that are subsequently stably incorporated into a liposomal vesicle for intravenous administration. The pharmacokinetic properties and immune stimulatory capacity of pro-drugs delivered via liposomes (SAProsomes) are enhanced compared to the free drug form. By performing efficacy screening among the SAProsomes incorporating different pro-drugs in syngeneic mouse tumor models, we find that superior therapeutic performance relies on improved delivery to the desired tumor and lymphoid compartments. The best candidate, SAProsome-3, highly stimulates secretion of inflammatory cytokines and creates a tumoricidal immune landscape. Notably, upon application to breast cancer or melanoma mouse models, SAProsome-3 elicits durable remission of established tumors and postsurgical tumor-free survival while decreasing metastatic burden without significant systemic toxicity. In summary, our work establishes the proof of principle for a better targeted and more efficient and safe STING agonist therapy. Agonists of the cytosolic DNA-sensing STING pathway potently remodel the tumour immune microenvironment to support anti-tumour adaptive immunity, but at the expense of adverse systemic inflammation. Here authors exchange the STING agonist MSA-2 with its prodrugs that are suitable for nano-liposomal delivery and thus achieve increased efficiency and decreased toxicity.